Barriers for Hispanic Caregivers With Obese Preschool Children. (September 2016) - White, Christina; Murphy, Taylor; Hodges, Eric A.; Berry, Diane C.
Introduction: Childhood obesity is a growing epidemic, and the rates are disproportionately higher in minorities. Clinical guidelines have contributed to decreased prevalence overall, but the rates in Hispanic preschoolers have increased. Method: This review of the literature summarizes the perceptions and beliefs of caregivers of Hispanic preschool children regarding weight status and feeding behaviors, as well as the perceived cultural barriers to guideline adherence. A search of the CINAHL, PubMed, Joanna Briggs, and Global Health databases identified studies performed between January 1, 2008, and April 1, 2016. Search terms included Hispanics, guideline adherence, gap, barriers, obesity, overweight, and attitude to obesity . Results: Fifteen studies met the inclusion criteria, including some about Hispanic caregivers of preschool-aged children. Several cultural perceptions and beliefs were identified. Conclusion: Further study is needed to develop more culturally relevant and sensitive guidelines and to design specific and effective interventions for this population.